A Comparative Performance Analysis of Torque Control Schemes for Induction Motor Drives - R Rajendran; Dr. N.Devarajan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper presents a comparative study of field-oriented control(FOC), conventional direct torque control(DTC) and proposed space vector modulated direct torque control with low pass filter(SVM-DTC). The main characteristics of FOC, DTC and proposed SVM-DTC schemes are studied by simulation, emphasizing their advantages and disadvantages. The performance of three control schemes is evaluated in terms of torque, current ripples and transient responses. It is shown that the proposed scheme improves the performance by combining a low torque, current ripple characteristics with fast torque dynamics.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.207